Meta-Analysis Study of Problem-Based Learning Models on Student's Mathematic Ability at Junior High School and High School Levels - Muhamad Wulidasauma Ajinegara; Ishaq Nuriadin (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2022)
This study aims to analyze the effect of problem-based learning models on students' mathematical abilities at the junior and senior high school levels. This research method uses a meta-analysis method with a sample of 15 articles in national journals and an instrument in the form of coding (code category) which is divided into several characteristics and calculates the effect size of each characteristic using the Glass formula. The results of this meta-analysis showed that the effect of problem-based learning models on students' mathematical abilities at the high school level was higher than junior high school education with students' critical thinking abilities having a higher influence than other mathematical abilities. Keywords: Problem Based Learning, Meta-Analysis, Mathematical Ability.